Penyuluhan dan Pembinaan Rohani Tentang Setia Kepada Allah Berdasarkan Amsal 3:1–8 di Gereja Kristen Ketapang Pos Duta Garden, Tangerang - Amirrudin Zalukhu (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
The spiritual counseling activity themed “Faithfulness to God in Proverbs 3:1–8” aims to explore the meaning of faithfulness from a Biblical perspective and its relevance to the daily lives of the congregation. Faithfulness to God is understood not merely as a moral obligation, but as a response arising from an intimate and deep relationship with God, manifested through a commitment to live according to His commands in every aspect of life. This activity employed a monologue sermon method, enriched with illustrations and personal testimonies to deepen the congregation’s understanding of the message delivered. Observations showed an increase in the comprehension of the verses discussed, deeper personal reflection, and a strengthened commitment among the congregation to live faithfully to God. Active participation in the form of questions and discussions indicated a positive reception of the message. The evaluation of the activity revealed that the implementation ran smoothly without significant obstacles. Recommended follow-up actions include further training on the theme of faithfulness, strengthening small groups or family Bible studies, and encouraging the congregation’s involvement in ministry as a tangible expression of their faithfulness to God. Thus, faithfulness to God is regarded as a foundational key to a blessed and peaceful life.